Maribor po prevratu in vladni komisar dr. Josip Leskovar - Friš, Darko (Studia Historica Slovenica, 2018)
Dr. Josip Leskovar was appointed government commissioner for Maribor in March 1920. He was in office for nine months until the end of December of the same year. At the beginning of January 1921, he handed over the tasks to the newly appointed commissioner, Ivo Poljanec. The article presents Leskovar's short biography, and on the basis of literature, newspaper sources, and archival material highlights some of the most important projects that were carried out in his time. Leskovar led preparations for the reception of Regent Alexander Karadjordjevic, who visited Maribor in June 1920, and in the city, in the summer, organized an all-Slovenian Orel Association camp and a gathering of the Sokol SHS Association. The biggest issues the city was facing were food, housing, and fuel shortages.
Keywords: Leskovar, Josip; občine; občinska uprava; Slovenija